A surface charge-switchable and folate modified system for co-delivery of proapoptosis peptide and p53 plasmid in cancer therapy. (January 2016) - Chen, Si; Rong, Lei; Lei, Qi; Cao, Peng-Xi; Qin, Si-Yong; Zheng, Di-Wei; Jia, Hui-Zhen; Zhu, Jing-Yi; Cheng, Si-Xue; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract: To improve the tumor therapeutic efficiency and reduce undesirable side effects, ternary FK/p53/PEG-PLL(DA) complexes with a detachable surface shielding layer were designed. The FK/p53/PEG-PLL(DA) complexes were fabricated by coating the folate incorporated positively charged FK/p53 complexes with charge-switchable PEG-shield (PEG-PLL(DA)) through electrostatic interaction. At the physiological pH 7.4 in the bloodstream, PEG-PLL(DA) could extend the circulating time by shielding the positively charged FK/p53 complexes. After the accumulation of the FK/p53/PEG-PLL(DA) complexes in tumor sites, tumor-acidity-triggered charge switch led to the detachment of PEG-PLL(DA) from the FK/p53 complexes, and resulted in efficient tumor cell entry by folate-mediated uptake and electrostatic attraction. Stimulated by the high content glutathione (GSH) in cytoplasm, the cleavage of disulfide bond resulted in the liberation of proapoptosis peptide C-KLA(TPP) and the p53 gene, which exerted the combined tumor therapy by regulating both intrinsic and extrinsic apoptotic pathways. Both in vitro and in vivo studies confirmed that the ternary detachable complexes FK/p53/PEG-PLL(DA) could enhance antitumor efficacy and reduce adverse effects to normal cells. These findings indicate that the tumor-triggered decomplexation of FK/p53/PEG-PLL(DA) supplies a useful strategy for targeting delivery of different therapeutic agents in synergetic anticancer therapy.